Rodrigo Duterte „független” külpolitikája – az amerikai-filippínó szövetség geostratégiai kihívásai a 21. században: THE "INDEPENDENT" FOREIGN POLICY OF RODRIGO DUTARTE - THE CHALLENGES OF THE US-FILIPINO ALLIANCE IN THE 21TH CENTURY - Klemensits, Péter (Közép-Európai Közlemények, 2020)
During the Cold War, the Philippines was an indispensable US ally, and this was still basically the case at the turn of the 21st century. However, the inauguration of President Rodrigo Duterte in June 2016 heralded great changes for the international position of the Philippines: a shift towards China and Russia occurred, followed by the emergence of a more balanced foreign policy. The partnership with the US has changed, too: during the Obama administration, the relationship between the two countries became cooler, although the foundations of the alliance were never contested. In the wake of Donald Trump’s assumption of office in January 2017, the alliance seems to have become as strong as before, and economic as well as security-military cooperation has continued. The author’s aim is to analyze the Philippines’ position in the US-led world order from 1945 to the present, as well as the foundations of the United States–Philippines special relationship. After that the main components of Duterte’s “independent” foreign policy and the fundamental changes in the Philippines’ foreign relations are presented. The analysis focuses on the causes of the conflict at the end of Barack Obama’s presidency, followed by the improving partnership during the Trump era and the main geopolitical challenges the alliance has had to face. According to its conclusion the US–Philippines security cooperation will remain strong under Presidents Duterte and Trump due to strategic considerations, which indicate the military alliance is in the interests of both nations.